5x+3-3x=9-x

Simple and best practice solution for 5x+3-3x=9-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3-3x=9-x equation:


Simplifying
5x + 3 + -3x = 9 + -1x

Reorder the terms:
3 + 5x + -3x = 9 + -1x

Combine like terms: 5x + -3x = 2x
3 + 2x = 9 + -1x

Solving
3 + 2x = 9 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + 2x + x = 9 + -1x + x

Combine like terms: 2x + x = 3x
3 + 3x = 9 + -1x + x

Combine like terms: -1x + x = 0
3 + 3x = 9 + 0
3 + 3x = 9

Add '-3' to each side of the equation.
3 + -3 + 3x = 9 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = 9 + -3
3x = 9 + -3

Combine like terms: 9 + -3 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| 2+y=19 | | x-6(-2x+2.5)=15 | | 4+8x=-24 | | 1.844=0.8193x-0.7785 | | 2x-7y=37 | | G+5=g-10 | | 3z+8=23 | | 1.927=0.8193x-0.7785 | | -5(x+7)=3x-3 | | 1.25=0.8193x-0.7785 | | x^2+kx+k^2=0 | | (8x)*(7y)= | | 47-17=5(x-2) | | (8x)x(7y)= | | x=0.8193y-0.7785 | | -12n+4=-8n-16 | | y=0.8193x-0.7785 | | 3x-9=10x-5 | | -3(1+6r)=-r | | 0.2(a-5)-0.1(3a+1)=0 | | 17x-5=8(2x-4) | | 136=x^2+9x | | 8g-6=5g+12 | | (z-6)(z-7)=0 | | 8x^-3yz^-6/4x^2yz | | (5w-8)(5+w)=0 | | 5ln(x-2)-ln(4-x^2)-3ln(x)= | | 70-5X=7+7x | | 13x-202=6x-6 | | 73-2x=9-10x | | 2x+25=7 | | D+250=020 |

Equations solver categories